The Determination of Macular Diseases with the Preoperative Optical Coherence Tomography in Patients Undergoing Cataract Surgery - Yusufoğlu, Elif; Kobat, Sabiha Güngör (Gazi Eye Foundation, 2025)
Purpose: To determine subclinical macular pathologies in patients undergoing cataract surgery with optical coherence tomography (OCT) Materials and Methods: The files of cases who underwent cataract surgery between July 2020 and December 2023 were examined. The eyes included in the study were those with no pathology determined in fundus examination, with no history of macular disease, and with adequate quality images obtained on OCT. The eyes were separated into two groups as those with and without pathology on OCT. The relationships between the prevalence of macular pathologies and potential risk factors were analyzed. Results: Evaluation was made of 705 eyes of 508 patients. Macular pathology was determined on the preoperative OCT in 79 (11.2%) patients. The most frequently seen pathologies were epiretinal membrane (29 eyes, 36.7%), age-related macular degeneration (23 eyes, 29.1%), and vitreomacular traction (9 eyes, 11.4%). The mean age of the cases determined with pathology was seen to be statistically significantly higher than that of the cases without pathology (p<0.001). No significant difference was determined between the two groups in respect of gender, preoperative visual acuity, and systemic diseases. Conclusion: In patients who are planned to cataract surgery, OCT is more sensitive than biomcroscopic fundus examination in the determination of macular pathologies. The preoperative determination of macular pathologies is important in terms of predicting visual outcomes, informing the patient of potential postoperative risks, and in deciding the type of lens to be used. Therefore, preoperative macular OCT should be added to the routine examination methods. © 2024 The author(s). ted use, distribution, and.
Keywords: Cataract; Maculopathy; Optical coherence tomography